THE DYNAMIC INFLUENCE OF INNOVATION AND RENEWABLE ENERGY CONSUMPTION ON SUSTAINABLE DEVELOPMENT: AN EVALUATION OF VIETNAM - Ngan, Dao Phuong; Huyen, Nguyen Thi Thanh; Nguyen, Nguyen Thao; Trang, Tran Mai (Graduate Program of Universitas Tarumanagara, 2024)
At the COP26, Prime Minister Pham Minh Chinh stressed the role of climate change and environmental management in economic growth. Vietnam has committed to a clean energy transition, phasing out coal, and achieving net-zero CO2 emissions by 2050, demonstrating its efforts to combat climate change. This paper aimed to explore the relationship between the change of CO2 emissions and factors including renewable energy consumption, population growth rate, GDP per capita, and innovative advances by using the ARDL model covering periods from 1990 to 2021. The results indicated that long-term increases in renewable energy and population growth can reduce CO2 emissions. However, a positive relationship is found between economic growth and CO2 emissions within the same period observed. Whereas innovation was not a determinant of CO2 emissions in the long run. In the shorter term, lags of renewable energy can lead to increased CO2 emissions while lags of innovation and economic growth exhibited a negative impact on emissions. Meanwhile, population growth’s lags have no significant effect on CO2 emissions. Based on these research findings, this paper suggested some comments on the transition to consumption of clean and renewable energy, hopefully achieving net zero by 2050.